The begging question : Sweden's social responses to the Roma destitute - Hansson, Erik (Cultural geographies + rewriting the Earth., 2023)
Erik Hansson examines Swedish society's reactions to the presence of European Union citizens, mainly Romanian and Bulgarian Roma, begging in the 2010s.